Enhanced Water Purification Performance of Ionic Liquid Impregnated Metal–Organic Framework: Dye Removal by [BMIM][PF6]/MIL-53(Al) Composite - Kavak, Safiyye; Durak, Özce; Kulak, Harun; Polat, H. Mert; Keskin, Seda; Uzun, Alper (Frontiers in Chemistry, 2021)
We incorporated a water-stable ionic liquid (IL), 1-butyl-3-methylimidazolium hexafluorophosphate, [BMIM][PF6], into a water-stable metal organic framework (MOF), MIL-53(Al), to generate the [BMIM][PF6]/MIL-53(Al) composite. This composite was examined for wastewater treatment by studying its capacity for methylene blue (MB) and methyl orange (MO) removal from aqueous solutions having either single dye or mixture of both. Data illustrated that the removal efficiency and the maximum adsorption capacity of MIL-53(Al) were increased several-times upon [BMIM][PF6] incorporation. For instance, within 1 min, 10 mg pristine MIL-53(Al) adsorbed 23.3% MB from 10 mg/L MB solution, while [BMIM][PF6]/MIL-53(Al) composite was adsorbing 82.3% MB in an identical solution. In the case of MO, 10 mg pristine MIL-53(Al) achieved 27.8 and 53.6% MO removal from 10 mg/L MO solution, while [BMIM][PF6]/MIL-53(Al) composite was removing 61.4 and 99.2% within 5 min and 3 h, respectively. Moreover, upon [BMIM][PF6] incorporation, the maximum MB and MO adsorption capacities of pristine MOF were increased from 84.5 and 44 mg/g to 204.9 and 60 mg/g, respectively. Adsorption of both dyes in pristine MIL-53(Al) and [BMIM][PF6]/MIL-53(Al) followed a pseudo-second-order kinetic model and Langmuir isotherm model. In a mixture of both dyes, the IL/MOF composite showed a doubled MB selectivity after the IL incorporation. Composite was successfully regenerated at least two-times after its use in wastewater treatment to remove MB, MO, and their mixtures. IR spectra indicated that the dye adsorption occurs on [BMIM][PF6]/MIL-53(Al) by electrostatic interactions, hydrogen bonding, hydrophobic interactions, and π−π interactions. These results showed that [BMIM][PF6]/MIL-53(Al) composite is a highly promising material for efficient wastewater treatment.